2009
DOI: 10.1002/lary.20535
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of seropositivity to bordetella pertussis and mycoplasma pneumoniae infection in patients with chronic laryngotracheitis

Abstract: Bordetella pertussis and mycoplasma pneumoniae infection play a significant role in the etiology of CLTR. Pertussis can be a mild but chronic presentation and may not produce typical symptoms of severe cough. Symptom duration and severity cannot differentiate between CLTR of infectious or other etiology. Infection should be considered in patients with CLTR that have significant tracheal erythema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…[2] Other etiologies of chronic laryngeal inflammation, such as allergies, inhaled irritants, and upper respiratory infections can cause signs and symptoms of laryngeal inflammation. [3] The prevalence of GERD in the United States is 10-20% as defined by weekly heartburn or acid regurgitation. [4] Selfreported symptoms of GERD do not correlate well with presence of pathologic reflux on objective testing.…”
Section: Original Articlementioning
confidence: 99%
“…[2] Other etiologies of chronic laryngeal inflammation, such as allergies, inhaled irritants, and upper respiratory infections can cause signs and symptoms of laryngeal inflammation. [3] The prevalence of GERD in the United States is 10-20% as defined by weekly heartburn or acid regurgitation. [4] Selfreported symptoms of GERD do not correlate well with presence of pathologic reflux on objective testing.…”
Section: Original Articlementioning
confidence: 99%
“…Mycoplasma pneumoniae was not found to be a significant etiological agent for chronic pharyngitis in this study. Beaver and Karow 6 demonstrated that 15% of patients with chronic pharyngitis had elevated IgM to M pneumoniae . They also inferred that individuals with allergies and silent laryngopharyngeal reflux have a more fragile pharyngeal mucosa and are consequently more prone to infection with Chlamydia 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, postmortem studies confirm the key role of the trachea in the natural history of pertussis [50]. The authors of a prospective study reported that among 54 adults presenting with chronic laryngotracheitis, 24% had elevated IgA and IgG levels and 15% had elevated anti-toxin pertussis IgM levels [51].…”
Section: Tracheal Infection During Pertussismentioning
confidence: 98%